2015
DOI: 10.1111/jog.12667
|View full text |Cite
|
Sign up to set email alerts
|

What is the role of matrix metalloproteinase‐2 in placenta percreta?

Abstract: The stronger expression of the MMP-2 enzyme in the PP as compared to the normal placental tissue suggests that this enzyme may be an effective mediator in the pathogenesis of PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
2
15
0
3
Order By: Relevance
“…Matrix metalloproteinase (MMP) is a group of enzymes that play an important role in the penetration of trophoblast cells by degrading the extracellular matrix [ 38 ]. Specifically, the gelatinases MMP-2 and MMP-9 are found in high concentrations in the placenta [ 39 ]. There is conflicting evidence about their significance in PAS.…”
Section: Molecular Biologymentioning
confidence: 99%
“…Matrix metalloproteinase (MMP) is a group of enzymes that play an important role in the penetration of trophoblast cells by degrading the extracellular matrix [ 38 ]. Specifically, the gelatinases MMP-2 and MMP-9 are found in high concentrations in the placenta [ 39 ]. There is conflicting evidence about their significance in PAS.…”
Section: Molecular Biologymentioning
confidence: 99%
“…Several studies reported possible molecular or genetic changes in PAS compared to normal controls, such as MMP2 might be increased in placenta percreta [23], or MicroRNA-34a might be decreased in placenta accreta [29], but they only compared the genetic changes between cases and controls in groups. In this study, the CTSV staining pattern in EVT was compared between the adherent site and the non-adherent site within identical cases, and the pattern was found to differ according to the adhesion status where EVT was located.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, only the results by immunohistochemical analysis could be recognized as the solid findings in this study. During placental development, proteases such as MMPs, plasminogen activators, or cathepsins have been reported to play important roles in the invasion of trophoblast by degrading extracellular matrix components and facilitating trophoblast penetration into the decidua [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…For all the study subjects, immunohistochemical evaluation was made of 5 fields selected at random from the sections of placental tissue at x400 original magnification.The immunohistochemical staining of osteopontin was evaluated with a semi-quantitative scoring system in which cytoplasmic staining intensity was categorised as negative (0), weakly positive (1+), moderately positive (2+) or strongly positive (3+). A result of > 50% of the cells with strong staining was determined as strongly positive (3+), < 25% as weakly positive (1+) and 25-50% as moderately positive (2+) [13].…”
Section: Immunohistochemical Scoringmentioning
confidence: 99%